Immunometabolic editing of the tumor microenvironment: from reprogramming mechanisms to therapeutic vulnerabilities - Li, Yixin; Zhang, Yunmei; Nie, Yan; Chen, Xueman (Frontiers in Immunology, 2026)
Metabolic reprogramming is not only one of the malignant characteristics of tumor cells, but also commonly seen in a variety of immune cells in tumor microenvironment(TME), which massively promotes tumor-body immune interaction. Immunometabolic editing is a dynamic, co-evolutionary process wherein adaptive metabolic reprogramming in the TME, driven by tumor-immune crosstalk during immunoediting, critically shapes anti-tumor immune response and governs immune evasion. Studies of metabolic pathways linked to anti-tumor immune process and discoveries of important therapeutic targets are conducive to the development of targeted immunometabolic intervention to enhance the body’s anti-tumor immune response and improve the efficacy of tumor immunotherapies. This review summarizes metabolic characteristics of the TME, highlights immunometabolic editing during cancer evolution, and discusses mechanisms by which tumor immunotherapies modulate tumor immunometabolism to identify potential therapeutic targets.